Strategi Manajemen Hubungan Masyarakat (HuMas) dalam Mengembangkan Hubungan Kerjasama Bidang Pendidikan di SMAN 2 Sangatta Utara - Cici Nuryathrib; Ramdanil Mubarok; Jumrianah Jumrianah (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2025)
The Strategy a set of actions taken to achieve goals. To realize this strategy, specific actions need to be by undertaken public relations management. The objective of this scientific article is to understand the public relations management strategies in developing educational cooperation relationships at SMAN 2 Sangatta Utara. The research is motivated by the importance of cooperation for the advancement and improvement of educational quality within school institutions. This qualitative field study involved the school principal, the vice principal for public relations, teachers, and partner representatives as informants. Data was collected through observation, interviews, and documentation. The findings indicate that SMA Negeri 2 Sangatta Utara maintains good cooperative relationships with various parties, including universities, the industrial and business sectors, and local government. The implemented PR strategies include actively preparing work program proposals, drafting Memorandums of Understanding (MoU), and conducting regular evaluations of involved teachers and students. However, challenges were encountered, namely budget limitations for MoU activities and coordination difficulties with the business/industry sectors regarding the improvement of teacher human resources and student funding. The proposed solutions involve continuously optimizing existing strategies, such as proposal submissions, MoU creation, and ongoing evaluations, to overcome these obstacles and strengthen educational cooperation